Reply to “comment on ‘arresting an unusual amide tautomer using divalent cations’” - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Seol, Jin Gyu; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
In our publication, we assigned the blue-shifted shoulder of N-methylacetamide (NMA) in the infrared (IR) spectrum (∼1645 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1) to an iminolate tautomer stabilized in the presence of divalent metal cations (e.g., 5 M Ca<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2+).<a class="ref ref1" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(1) Cremer and co-workers comment that this shoulder arises from the dehydration of the amide oxygen upon interaction with the metal cations.<a class="ref ref1a ref2" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(2,3) Their assignment is based on three interesting experimental observations: (1) the IR spectrum of <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-isotope-labeled NMA does not show any considerable red-shift compared to that of NMA; (2) a new peak appears for NMA at 1680 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 in the presence of 1 M DCl, which shows a 17 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 red-shift for <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-labeled NMA; and (3) the IR spectrum of acetone C═O stretch also demonstrates a blue-shifted shoulder in the presence of a high concentration of CaCl<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2.